2016
DOI: 10.5115/acb.2016.49.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mesenchymal cells beneath cornification of the fetal epithelium and epidermis at the face: an immunohistochemical study using human fetal specimens

Abstract: Fetal development of the face involves a specific type of cornification in which keratinocytes provide a mass or plug to fill a cavity. The epithelial-mesenchymal interaction was likely to be different from that in the usual skin. We examined expression of intermediate filaments and other mesenchymal markers beneath cornification in the fetal face. Using sections from 5 mid-term human fetuses at 14–16 weeks, immunohistochemistry was conducted for cytokeratins (CK), vimentin, nestin, glial fibrilary acidic prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
(37 reference statements)
2
13
0
Order By: Relevance
“…The presence of the embryonic nasal plug is a common transient embryonic feature of amniotes. It has been found in snakes [ 66 , 69 , 72 ], lizards [ 19 , 73 ], turtle [ 69 ], Sphenodon [ 74 ] , birds [ 71 , 72 ] and mammals [ 72 , 75 ] including human [ 76 , 77 ]. The nature of the nasal plug is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the embryonic nasal plug is a common transient embryonic feature of amniotes. It has been found in snakes [ 66 , 69 , 72 ], lizards [ 19 , 73 ], turtle [ 69 ], Sphenodon [ 74 ] , birds [ 71 , 72 ] and mammals [ 72 , 75 ] including human [ 76 , 77 ]. The nature of the nasal plug is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin has also been found in preneoplastic lesions of oral epithelium and possibly is associated with differentiation, invasion and poorer prognosis in oral squamous cell carcinoma (Ravindran & Devaraj, 2015). In the facial tissue of 14 to 16 weeks old human fetuses using immunohistochemistry nestin-reactivity was seen in striated muscles, mesenchymal cells and fibers and the basal layer of the skin (Kim et al, 2016). In our study tissue samples showed prominent immunoreactivity for nestin with overall total number of nestin-positive structures higher in CBCLP tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the embryonic nasal plug is a common transient embryonic feature of amniotes. It has been found in snakes [66,69,72], lizards [18,73], turtle [69], Sphenodon [74], birds [71,72] and mammals [72,75] including human [76,77]. The nature of the nasal plug is poorly understood.…”
Section: Initial Fusion and Formation Of The Vestibulummentioning
confidence: 99%
“…The nature of the nasal plug is poorly understood. It is described as mass of epithelial cells [75], mass of isodiametric cells [21], peridermal plug [72,78], or structure formed by keratinocytes [77]. It has been proposed that it forms between the nasal prominences from the epithelial seam, which does not undergo disintegration [71,72], or as a proliferation of the "invaginated" oral epithelium [78], which in fact may be considered as walls of the presumptive vestibulum.…”
Section: Initial Fusion and Formation Of The Vestibulummentioning
confidence: 99%